Diagrama de flujo como parte de la estrategia metodológica para fortalecer el aprendizaje de las cadenas alimenticias, en los estudiantes del octavo grado de educación general básica paralelo “c” del centro de formación artesanal Monseñor Francisco Valdivieso Alvarado de la ciudad de Loja, periodo 2014 -2015. - Suquilanda Chocho, Stalin Jhonathan (2016)
The current education and teaching profession has always needed the provision of a wide range of methodological strategies, for the improvement of the educational activity, which allow them to facilitate the teaching-learning process. Within these strategies are graphic organizers, such as the flow diagram, which, when used as such strategy develops cognitive skills, teach students to clarify their thinking, and process, organize and prioritize new information. The present research work has the purpose of demonstrating that the use of the flow diagram contributes to the achievement of significant learning in the teaching of food chains. According to what was expressed in the previous paragraph, the present research had as its object the study of the following topic: FLOW DIAGRAM AS PART OF THE METHODOLOGICAL STRATEGY TO STRENGTHEN THE LEARNING OF THE FOOD CHAINS, IN THE STUDENTS OF THE EIGHTH GRADE OF BASIC GENERAL EDUCATION " C "OF THE TRAINING CENTER" MONSEÑOR FRANCISCO VALDIVIESO ALVARADO "OF THE CITY OF SHOP, PERIOD 2014 -2015. The general objective was to: Apply the flow diagram as part of the methodological strategy to strengthen the learning of food chains in the eighth grade students of the Parallel Primary Education "C" of the handicraft training center "Monseñor Francisco Valdivieso Alvarado "of the city of Loja, period 2014 -2015. In the development of the research, the following methods were taken into account: analytical, synthetic, deductive and inductive, which served to present and contrast the information obtained through bibliographic sources such as books, web pages, magazines and documents. As a technique the survey was used and as a tool for collecting the information the questionnaire, the bibliographic technique was used for the construction of the theoretical framework. We worked with 17 students and 1 teacher of the school, object of investigation. Finally, with the analysis, discussion and interpretation of the data, it was determined that students have little knowledge about food chains, this implies that the teacher does not apply the flow diagram in the teaching-learning process, limiting the development of different types of Skills in students. Applied the methodological strategy flow diagram, in the mentioned subject, evidencing that the students obtained a better understanding and assimilation of the information,which was demonstrated with the application of the technique of statistical correlation (pos test). Before this we can mention that the flow diagram improved the learning in the students of the eighth grade of Basic General Education of the training center "Monseñor Francisco V